A STUDY ON EEG CHANGES BEFORE AND AFTER EXAMINATION IN MEDICAL STUDENTS OF PANIPAT, HARYANA. - Ritu Soni; Itika Singh; Shyam Sunder Nagpal (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Medical education is globally recognized as highly stressful, with examination periods significantly intensifying stress levels. Stress can alter brain activity, which can be measured using electroencephalogram (EEG), a non-invasive tool that records spontaneous electrical activity of the brain from the scalp.Objective: To evaluate the changes in EEG wave patterns in medical students before and after examinations.Materials and Methods: The study will be conducted in the Neurophysiology laboratory, Department of Physiology, NCMCH, Panipat. A total of 20 medical students aged 18–22 years will be enrolled. EEG recordings will be obtained prior to the commencement of examinations and immediately after their completion. The variations in EEG waveforms will be analyzed to assess stress-related changes in neural activity.Results: It is expected that EEG recordings will show distinct alterations in brain wave patterns, reflecting increased stress levels before examinations compared to after their completion.Conclusion: Examination stress significantly affects EEG wave patterns in medical students. Recognition of such changes may help in devising strategies to reduce stress and anxiety, thereby improving academic performance and psychological well-being.